Irregularities in Indonesian Government Policy on Authorizing Religious Mass Organizations in Mining Concessions - Cicik Sulfa Dewi; Bagus Teguh Santoso (Fakultas Hukum Universitas Bhayangkara Surabaya, 2025)
This study examines the involvement of religious-based community organizations (Ormas Keagamaan) in the management of mineral and coal resources, based on Government Regulation No. 25 of 2024, which grants priority access to Special Mining Business Permit Areas (WIUPK) for business entities owned by such organizations. The research aims to analyze the legal limitations governing this policy and identify potential discriminatory aspects in its implementation. This normative legal research applies a juridical approach, focusing on the analysis of mining regulations, principles of good governance, and justice in natural resource management. The findings indicate that the policy was formulated hastily and without a transparent or participatory process. The existing regulatory framework does not clearly define selection mechanisms, eligibility indicators, or accountability procedures for religious organizations granted such privileges. Although these organizations are required to establish legal business entities, the exclusive prioritization raises concerns of discrimination against non-religious organizations and other qualified actors. Moreover, the limited technical capacity and professionalism of religious organizations further exacerbate the risks of weak governance and oversight in this strategic sector. Therefore, the policy should be reconsidered and strengthened through stricter, more inclusive, and accountable regulation to align with the principles of social justice, legal equality, and sustainable resource management.